2017
DOI: 10.1038/cddis.2017.416
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomotropism depends on glucose: a chloroquine resistance mechanism

Abstract: There has been long-standing interest in targeting pro-survival autophagy as a combinational cancer therapeutic strategy. Clinical trials are in progress testing chloroquine (CQ) or its derivatives in combination with chemo- or radiotherapy for solid and haematological cancers. Although CQ has shown efficacy in preclinical models, its mechanism of action remains equivocal. Here, we tested how effectively CQ sensitises metastatic breast cancer cells to further stress conditions such as ionising irradiation, dox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 79 publications
2
37
0
Order By: Relevance
“…AQ is more cytotoxic against cancer cells than CQ [18,44], albeit AQ displays similar or lower autophagy/lysosome inhibition [18,44]. Unlike for AQ, the CQ-induced cell death depends on glucose [44]. These differences suggest that the unique impact of AQ on rDNA transcription may explain its higher cytotoxicity.…”
Section: Aq Kills Crc Cellsmentioning
confidence: 98%
“…AQ is more cytotoxic against cancer cells than CQ [18,44], albeit AQ displays similar or lower autophagy/lysosome inhibition [18,44]. Unlike for AQ, the CQ-induced cell death depends on glucose [44]. These differences suggest that the unique impact of AQ on rDNA transcription may explain its higher cytotoxicity.…”
Section: Aq Kills Crc Cellsmentioning
confidence: 98%
“…This axis may therefore represent a potential therapeutic target for treatment of metastatic breast cancer (88). It has been reported that inhibition of hexokinase using 2-deoxyglucose induces chloroquine-resistance in breast cancer (89). In addition, metformin stimulates the glycolytic flux caused by starvation by interfering with HK2 activity (90).…”
Section: Ppp In Malignant Tumorsmentioning
confidence: 99%
“…For Gal-3 puncta tests, HeLa cells plated on glass coverslips were transfected with pEGFP-hGal3 (Addgene: 73080) (45) using Lipofectamine 2000 according to standard protocols, as we have previously reported (42). After 24 hours of transfection, cells were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the Galectin family of beta-galactoside-binding proteins have served as useful tools to detect damage of endomembranes such as lysosomes. (42)(43)(44)(45). Galectin-8 plays a critical role as receptor for targeting damaged SCV to the xenophagy pathway (46).…”
Section: After Characterizing Escape Of Wildtypementioning
confidence: 99%
See 1 more Smart Citation